2016
DOI: 10.1371/journal.pgen.1006226
|View full text |Cite|
|
Sign up to set email alerts
|

Mek1 Down Regulates Rad51 Activity during Yeast Meiosis by Phosphorylation of Hed1

Abstract: During meiosis, programmed double strand breaks (DSBs) are repaired preferentially between homologs to generate crossovers that promote proper chromosome segregation at Meiosis I. In many organisms, there are two strand exchange proteins, Rad51 and the meiosis-specific Dmc1, required for interhomolog (IH) bias. This bias requires the presence, but not the strand exchange activity of Rad51, while Dmc1 is responsible for the bulk of meiotic recombination. How these activities are regulated is less well establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(168 citation statements)
references
References 83 publications
(159 reference statements)
9
157
0
Order By: Relevance
“…This hypothesis is supported by the observation that Dmc1 foci formation is compromised in vivo when Rad51 is absent (7,18), the finding that Rad51 is downregulated by Hed1 and Mek1 during meiosis (14,16,17), and the finding that Rad51 strand invasion activity is not required during meiosis (13). We wanted to test the possibility that Dmc1 might also exert some influence over Rad51 by comparing the disassembly rates of Rad51 only, Dmc1 only, and mixed filaments containing both recombinases.…”
Section: Models For Mixed Recombinase Filaments -Rad51mentioning
confidence: 96%
See 1 more Smart Citation
“…This hypothesis is supported by the observation that Dmc1 foci formation is compromised in vivo when Rad51 is absent (7,18), the finding that Rad51 is downregulated by Hed1 and Mek1 during meiosis (14,16,17), and the finding that Rad51 strand invasion activity is not required during meiosis (13). We wanted to test the possibility that Dmc1 might also exert some influence over Rad51 by comparing the disassembly rates of Rad51 only, Dmc1 only, and mixed filaments containing both recombinases.…”
Section: Models For Mixed Recombinase Filaments -Rad51mentioning
confidence: 96%
“…Despite these many commonalities, Dmc1 is the recombinase responsible for performing strand invasion during meiosis (13). In contrast, Rad51 is actively downregulated by Hed1-and Mek1-mediated inhibition of its interactions with Rad54, which is a cofactor that is required for Rad51 strand invasion activity (11,(14)(15)(16)(17). However, Rad51 is required for normal progression through meiosis and promotes Dmc1 foci formation, consistent with a role for Rad51 as a Dmc1 accessory factor (6,7,13,18).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and biochemical studies have shown that Hed1 interacts with Rad51 and inhibits strand exchange activity by preventing Rad54 from associating with the presynaptic complex (Tsubouchi & Roeder, 2006;Busygina et al, 2008Busygina et al, , 2012Callender et al, 2016).…”
Section: Hed1 Interacts Tightly With the Rad51 Presynaptic Complexmentioning
confidence: 99%
“…In support of this model, we find that Rad54 and Hed1 binding interactions are mutually exclusive, and once established, these binding interactions are effectively irreversible over the time scales that might be relevant to meiotic progression ( Fig 7B). Reactivation of Rad51 coincides with inactivation of Mek1, and as a result, Rad54 phosphorylation and Hed1 phosphorylation are lost, and Hed1 is degraded (Callender et al, 2016;Argunhan et al, 2017;Prugar et al, 2017). Interestingly, Rad51 plays a late role in meiotic prophase by repairing residual DSBs after disassembly of the synaptonemal complex (Argunhan et al, 2017;Prugar et al, 2017).…”
Section: Transition From Mitotic To Meiotic Presynaptic Filamentsmentioning
confidence: 99%
See 1 more Smart Citation